To Compare the Frequency of Deep Surgical Wound Infection in Patients Undergoing Laparotomy With or Without Post-Operative Drain (Medical Forum Monthly, 2024)
Objective: To examine the frequency of deep surgical wound infection in patients underwent laparotomy procedure with or without post-operative drain.Study Design: Comparative/observationalPlace and Duration of Study: This study was conducted at the Department of Surgery Unit-1, Sandeman Provincial Civil Hospital, Quetta from January 2017 to June 2018.Materials and Methods: One hundred and forty patients of both genders with ages 15 to 60 years whom were received laparotomy treatment due to intra-abdominal infection or complicated appendicitis were included in this study. Patient’s medical history, age, sex and residency were recorded after taking informed consent. All the patients were divided into two groups, Group I contained 70 patients and received post-operative drain and Group II contains 70 patients and received laparotomy without drain. Deep surgical wound infection was examined at 7th day after surgery and compare between both groups.Results: Ninety (64.28%) patients 43 in Group I and 47 in Group II were males and 50 (35.72%) patients 27 in Group I and 23 in Group II were females. In Group I and II 25 and 27 patients were ages 15 to 30 years, 30 and 28 patients had ages 36 to 45 years, 15 and 15 patients were ages between 46 to 60 years. 8 (11.43%) patients in Group I and 10 (14.29%) patients had deep surgical infection within 1 week after surgery. Statistically there is no significant difference between the both groups (p>0.356)Conclusion: There is no difference in developing deep surgical site infection in patients undergoing laparotomy with drain or without drain placement.